2014
DOI: 10.1109/taslp.2013.2295914
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility Prediction Based on Mutual Information

Abstract: This paper deals with the problem of predicting the average intelligibility of noisy and potentially processed speech signals, as observed by a group of normal hearing listeners. We propose a model which performs this prediction based on the hypothesis that intelligibility is monotonically related to the mutual information between critical-band amplitude envelopes of the clean signal and the corresponding noisy/processed signal. The resulting intelligibility predictor turns out to be a simple function of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…Recently, information theory (IT) has been proposed as a new paradigm for speech intelligibility prediction [13,14,15]. This is a natural approach to take given that the fundamental goal of speech communication is to transfer information from a talker to a listener.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, information theory (IT) has been proposed as a new paradigm for speech intelligibility prediction [13,14,15]. This is a natural approach to take given that the fundamental goal of speech communication is to transfer information from a talker to a listener.…”
Section: Introductionmentioning
confidence: 99%
“…First, several studies have suggested that IT could provide a unified point of view. In [16] and [17] it was observed that the AI resembles the Shannon capacity of a memoryless Gaussian channel, and in [14] it was shown that STOI is related to the average amount of information shared between the temporal envelopes of clean and distorted speech signals. Second, IT provides a powerful theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent measures estimate in each frequency band the correlation (e.g. Short-Time Objective Intelligibility, STOI [4]) or the mutual information (SIMI [5]) between the clean and the distorted signals.…”
Section: Introductionmentioning
confidence: 99%